Evaluation of caries risk factors associated with pregnancy - Rivera, Karin Behnke; González López, Blanca Silvia; Sánchez vargas, Luis Octavio; Alanís Tavira, Jorge; Bermeo Escalona, Josue Roberto (CIENCIA ergo-sum; Vol. 26 Núm. 3 (2019): CIENCIA ergo-sum (noviembre 2019-febrero 2020), 2019)
Tooth decay is a serious public health problem, and identifying risk factors to the disease in pregnant women is essential. The use of the Cariogram, could contribute to implementing preventive measures to improve women’s health during pregnancy. The purpose of this study was to determine the risk to dental caries in pregnant women. The Cariogram presents the results of the five risk factors of caries, and it was observed that the patients have a 42% of chance to avoid new carious lesions and 58% could present lesions, which could be caused by 40% related to diet and bacteria. Conclusion: To date, existing studies are not sufficient to ultimately identify main caries risk factors associated with dental decay in pregnant women.